Prediction of the Solubility, Activity Coefficient and Liquid/Liquid Partition Coefficient of Organic Compounds - Hilal, S. H.; Karickhoff, S. W.; Carreira, L. A. (QSAR & combinatorial science, 2004)
Solvation models, based on fundamental chemical structure theory, were developed in the SPARC mechanistic tool box to predict a large array of physical properties of organic compounds in water and in non‐aqueous solvents strictly from molecular structure. The SPARC self‐interaction solvation models that describe the intermolecular interaction between like molecules (solute‐solute or solvent‐solvent) were extended to quantify solute‐solvent interaction energy in order to estimate the activity coefficient in almost any solvent. Solvation models that include dispersion, induction, dipole‐dipole and hydrogen bonding interactions are used to describe the intermolecular interaction upon placing an organic solute molecule in any single or mixed solvent system. In addition to estimation of the activity coefficient for 2674 organic compounds, these solvation models were validated on solubility and liquid/liquid distribution coefficient in more than 163 solvents including water. The RMS deviations of the calculated versus observed activity coefficients, solubilities and liquid/liquid distribution coefficients were 0.272 log mole fraction, 0.487 log mole fraction and 0.44 log units, respectively.